Clinical leadership style and hand hygiene compliance. Issue 1 (28th January 2014) - Christiana Stevens, Stella; Hemmings, Lynn; Scott, Claire; Lawler, Anthony; White, Craig
Abstract : Purpose: – The purpose of this paper is to investigate to what extent an engaging or authentic leadership style is related to higher levels of patient safety performance. Design/methodology/approach: – A survey and/or interview of 53 medical and dental staff on their perceptions of leadership style in their unit was conducted. Scores obtained from 51 responses were averaged for each question and overall performance was compared with unit specific hand hygiene (HH) compliance data. Interview material was transcribed and analysed independently by each member of the research team. Findings: – A modest negative relationship between this leadership style and hand hygiene compliance rates ( r =0.37) was found. Interview data revealed that environmental factors, role modelling by the leader and education to counter false beliefs about hand hygiene and infection control may be more important determinants of patient safety performance in this regard than actual overall leadership style. Research limitations/implications: – The sample was relatively small, other attributes of leaders were not investigated. Practical implications: – Leadership development for clinicians may need to focus on situational or adaptive capacity rather than a specific style. In the case of improving patient safety through increasing HH compliance, a more directive approach with clear statements backed up by role modelling appears likely to produce better rates. Originality/value: – Little is known about patient safety and clinical leadership. Much of the current focus is on developing transformational, authentic or engaging style. This study provides some evidence that it should not be used exclusively.